Bacterial contamination of platelets for transfusion: strategies for prevention - Jerrold H. Levy; Matthew D. Neal; Jay H. Herman (Critical Care, 2018)
Abstract Platelet transfusions carry greater risks of infection, sepsis, and death than any other blood product, owing primarily to bacterial contamination. Many patients may be at particular risk, including critically ill patients in the intensive care unit. This narrative review provides an overview of the problem and an update on strategies for the prevention, detection, and reduction/inactivation of bacterial contaminants in platelets. Bacterial contamination and septic transfusion reactions are major sources of morbidity and mortality. Between 1:1000 and 1:2500 platelet units are bacterially contaminated. The skin bacterial microflora is a primary source of contamination, and enteric contaminants are rare but may be clinically devastating, while platelet storage conditions can support bacterial growth. Donor selection, blood diversion, and hemovigilance are effective but have limitations. Biofilm-producing species can adhere to biological and non-biological surfaces and evade detection. Primary bacterial culture testing of apheresis platelets is in routine use in the US. Pathogen reduction/inactivation technologies compatible with platelets use ultraviolet light-based mechanisms to target nucleic acids of contaminating bacteria and other pathogens. These methods have demonstrated safety and efficacy and represent a proactive approach for inactivating contaminants before transfusion to prevent transfusion-transmitted infections. One system, which combines ultraviolet A and amotosalen for broad-spectrum pathogen inactivation, is approved in both the US and Europe. Current US Food and Drug Administration recommendations advocate enhanced bacterial testing or pathogen reduction/inactivation strategies (or both) to further improve platelet safety. Risks of bacterial contamination of platelets and transfusion-transmitted infections have been significantly mitigated, but not eliminated, by improvements in prevention and detection strategies. Regulatory-approved technologies for pathogen reduction/inactivation have further enhanced the safety of platelet transfusions. Ongoing development of these technologies holds great promise.